2007
DOI: 10.1186/1471-2180-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal action of positive and negative ions in air

Abstract: Background: In recent years there has been renewed interest in the use of air ionisers to control of the spread of airborne infection. One characteristic of air ions which has been widely reported is their apparent biocidal action. However, whilst the body of evidence suggests a biocidal effect in the presence of air ions the physical and biological mechanisms involved remain unclear. In particular, it is not clear which of several possible mechanisms of electrical origin (i.e. the action of the ions, the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 9 publications
(14 reference statements)
2
75
2
1
Order By: Relevance
“…Exposure to air ions for 15 minutes results in the inactivation of more than 80% of microorganisms on agar plates (Fletcher et al, 2007). Various studies have reported that air ions inhibit the growth of bacterial and fungal species (Shargawi et al, 1999;Noyce and Hughes, 2002;Kerr et al, 2006).…”
Section: Ion Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to air ions for 15 minutes results in the inactivation of more than 80% of microorganisms on agar plates (Fletcher et al, 2007). Various studies have reported that air ions inhibit the growth of bacterial and fungal species (Shargawi et al, 1999;Noyce and Hughes, 2002;Kerr et al, 2006).…”
Section: Ion Emissionmentioning
confidence: 99%
“…Further, there are few data on the effects of air ions on bioaerosols (not static microorganisms on agar plates, but airborne microorganisms). Fletcher et al (2007) suggested that air ions demonstrate bactericidal effects through the electro-poration of bacteria in addition to ozone exposure. Kim et al (2011) suggested that electro-poration plays a primary role in the antibacterial effects of air ions.…”
Section: Ion Emissionmentioning
confidence: 99%
“…For example, NAI play a positive role in altering the concentration of serotonin and cyclic nucleotides in the cerebral cortex of rats [6]. After that, various researchers demonstrated that NAI inhibit the growth of microorganism [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Air ions have long been considered as antimicrobial stimuli; however, the detailed mechanisms underlying the antimicrobial activity of air ions are under investigation (Lee, 2011). Fletcher et al (2007) suggested that air ions exert bactericidal effects via the electro-poration of bacterial cells. The position and accumulation of air ions on the surfaces of airborne microorganisms may disrupt the electric fields of adjacent cell walls, which in turn may disrupt the transport of electrons and protons inside the cells (Lee, 2011).…”
Section: Effect Of the Sequence Of Unipolar Ion Emission And Bioaerosmentioning
confidence: 99%